Land rights now : the Aboriginal fight for land in Australia. - International Work Group for Indigenous Affairs (Copenhagen : International Work Group for Indigenous Affairs, 1985)
Annotation pending.
Spine title: Australia.
Includes bibliographies.
Keywords: Aboriginal Australians -- Land tenure; Land rights - Pastoral industry; Land rights; Politics and Government - Political action - Land rights; Land rights - Mining industry